PENGARUH RISIKO KREDIT, MINIMALISASI RISIKO, PERTUMBUHAN PRODUK DOMESTIK BRUTO, DAN INFLASI TERHADAP PENDAPATAN BUNGA BERSIH PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2016 - Devi Widyawati; Desta Rizky Kusuma (Jurnal Fokus Manajemen Bisnis, 2017)
The aim of this research is to examine empirically the impact of credit risk, risk aversion, gross domestic product (GDP) growth, and inflation to Net Interest Margin on banking companies enlisted in BEI year 2013-2016. The factors that influenced NIM is credit risk which is proxied with NPL (Non Performing Loan) ratio, risk aversion which is proxied with CAR (Capital Adequacy Ratio), GDP growth and inflation. The period used is from 2013-2016.This research is causal research, that is to find recausality of independent and dependent variable. The population is 42 banking companies. The sampling method used is purposive sampling method. Based on the criteria, there are 41 banking companies. The hypothesis trial is done by the analysis of data panel regression an before do it, the research did a classic assumption trial. The result of hypothesis trial is done partially is t-test showed that NPL has t-statistic score is 1,4136 and t-tabel score is 1,290 on alpha 10% , so NPL has positive impact to NIM. CAR has t-statistic score is -0,2698 and t-tabel score is 1,290 on alpha 10%, so CAR doesn’t have impact to NIM. GDP growth has t-statistic score is 2,9349 and t-tabel score has 1,290 on alpha 10%, so GDP growth has positive impact to NIM. Inflation has t-statistic -0,5184 and t-tabel score is 1,290 on alpha 10%, so inflation doesn’t have impact to NIM.